Evaluation of the Effect of Ultra-Processed Food (UPF) Consumption of Cardiometabolic Risk in Professional Nigerian Adults: A Quantitative Study - Edem , Asukwo Asukwo; Marc , Chrysanthou; Mgbang , John Edward; Inyang , Aniekeme N‎disa (International Journal of Basic and Applied Sciences, 2025)
Background and objectives: to evaluate the effect of ultra-processed food (UPF) consumption on cardio-metabolic risk in professional Nigerian adults. Methods: Using standard methods, frequency, prevalence, and health implications of UPF consumption of ‎respondents were determined. A cross-sectional study design was adopted, with a simple random sampling ‎method in selecting 250 participants from five faculties in the College of Medical Sciences, University of ‎Calabar, Nigeria. Data were collected using a structured web-based questionnaire, collated using Microsoft Excel ‎software, and analysed using a combination of Chi-square (X2) test, one-sample t-test, and Pearson’s correlation ‎analysis using SPSS software.‎ Findings: The overall frequency of UPF intake was relatively low, with a significant (P<0.05) relationship with ‎participants’ age. The impact of participants’ UPF consumption frequency on body mass index, systolic, and ‎diastolic blood pressure was insignificant (P >0.05). The participants’ high level of knowledge of UPFs is a key ‎factor in explaining this finding. However, a significant (P<0.05) moderate correlation between BMI and ‎systolic blood pressure was observed, which is consistent with existing information in scientific literature.‎ Conclusion: This study revealed that the overall UPF consumption frequency was significantly low, which ‎correlated positively with the low BMI and BP, which may be due to a high level of knowledge of UPF ‎consumption and its effect on overall health. However, the study recommends a similar study with a larger sample ‎size‎.